Hacia una poética del relato didáctico : ocho estudios sobre El Conde Lucanor - Biglieri, Aníbal A. (Book collections on Project MUSE., 1989)
Through close readings of eight tales from the Conde Lucanor, Anibal A. Biglieri offers the foundation for a Poetics of short didactic narratives. Biglieri's point of entry into this canonical work is his analysis of the text's unique relation with reality. This book also offers insights about the significance of the frame story, the ethics of social position, and the relationship between the author and his text. Hacia una poetica del relato didictico reaffirms the foundational role that El Conde Lucanor plays in the development of narrative structures, and celebrates the complexity of this quintessential landmark of Hispanic literature.